Pyrosequencing of Mytilus galloprovincialis cDNAs: Tissue-Specific Expression Patterns - Craft, John A. (Public Library of Science, 2010)
BACKGROUND: Mytilus species are important in marine ecology and in environmental quality assessment, yet their molecular biology is poorly understood. Molecular aspects of their reproduction, hybridisation between species, mitochondrial inheritance, skewed sex ratios of offspring and adaptation to climatic and pollution factors are priority areas. METHODOLOGY/PRINCIPAL FINDINGS: To start to address this situation, expressed genetic transcripts from M. galloprovincialis were pyrosequenced. Transcripts were isolated from the digestive gland, foot, gill and mantle of both male and female mussels. In total, 175,547 sequences were obtained and for foot and mantle, 90% of the sequences could be assembled into contiguous fragments but this reduced to 75% for the digestive gland and gill. Transcripts relating to protein metabolism and respiration dominated including ribosomal proteins, cytochrome oxidases and NADH dehydrogenase subunits. Tissue specific variation was identified in transcripts associated with mitochondrial energy metabolism, with the digestive gland and gill having the greatest transcript abundance. Using fragment recruitment it was also possible to identify sites of potential small RNAs involved in mitochondrial transcriptional regulation. Sex ratios based on Vitelline Envelop Receptor for Lysin and Vitelline Coat Lysin transcript abundances, indicated that an equal sex distribution was maintained. Taxonomic profiling of the M. galloprovincialis tissues highlighted an abundant microbial flora associated with the digestive gland. Profiling of the tissues for genes involved in intermediary metabolism demonstrated that the gill and digestive gland were more similar to each other than to the other two tissues, and specifically the foot transcriptome was most dissimilar. CONCLUSIONS: Pyrosequencing has provided extensive genomic information for M. galloprovincialis and generated novel observations on expression of different tissues, mitochondria and associated microorganisms. It will also facilitate the much needed production of an oligonucleotide microarray for the organism.